Root Cause Failure Analysis of Stator Winding Insulation Failure on 6.2 MW Hydropower Generator - Agus Adhi Nugroho; Ida Widihastuti; As Ary (IAES Indonesia Section, 2016)
Insulation failure on generator winding insulation occurred in the Wonogiri Hydropower plant has caused stator damage since ase was short circuited to ground. The fault has made the generator stop to operate. Wonogiri Hydropower plant is one of the hydroelectric plants run by PT. Indonesia Power UBP Mrica with capacity 2 × 6.2 MW. To prevent damage to occur again on hydropower generators, an analysis is carried out using Root Cause Failure Analysis RCFA is a systematic approach to identify the root cause of the main orbasic root cause of a problem or a condition that is not wanted. There are several aspects to concerned such as: loading pattern and operations, protection systems, generator insulation resistance, vibration, the cleanliness of the air and the ambient air. Insulation damage caused by gradual inhomogeneous cooling at the surface of winding may lead in to partial discharge. In homogeneous cooling may present due to lattice hampered by dust and oil deposits. To avoid repetitive defects and unwanted condition above, it is necessary to perform major maintenance overhaul every 5000-6000 hours of operation.